Aplikasi Penanganan dan Pendampingan Korban Kekerasan Seksual Berbasis Web dan Android - Bastian, Alvian; Simamora, Rebeka Frederika; Ahyar, Muh; Ismail, Ismalandari (Smart Comp :Jurnalnya Orang Pintar Komputer, 2024)
In an effort to prevent and handle sexual violence and support the Regulation of the Minister of Education and Culture, Research and Technology concerning the Prevention and Handling of Sexual Violence, an application media is needed that allows survivors of sexual violence to report sexual crimes and receive psychological assistance. The purpose of this research is to create a media application that can help survivors of sexual violence get help and assistance as well as a medium for sharing stories so that other users can be more aware of the dangers of sexual violence. The method used in this research is using Android Studio and Visual Studio Code as an Integrated Development Environment (IDE) based on Android and using a no-relational (NoSQL) realtime database on firebase and MySQL database. The advantage of the research is that the system to be developed does not use physical servers anymore but all databases are stored in the cloud system. To help survivors to report sexual violence, this application makes it easy to contact law enforcement, contact a psychologist for psychological assistance via online chat, contact the nearest health facility, and contact the Women and Children Protection Unit. Based on testing, applications built based on android and websites can be concluded that they can run well and can be used as reporting and consulting media for survivors of sexual violence